Acute tau knockdown in the hippocampus of adult mice causes learning and memory deficits. Issue 4 (10th May 2018) - Velazquez, Ramon; Ferreira, Eric; Tran, An; Turner, Emily C.; Belfiore, Ramona; Branca, Caterina; Oddo, Salvatore
Summary: Misfolded and hyperphosphorylated tau accumulates in several neurodegenerative disorders including Alzheimer's disease, frontotemporal dementia with Parkinsonism, corticobasal degeneration, progressive supranuclear palsy, Down syndrome, and Pick's disease. Tau is a microtubule‐binding protein, and its role in microtubule stabilization is well defined. In contrast, while growing evidence suggests that tau is also involved in synaptic physiology, a complete assessment of tau function in the adult brain has been hampered by robust developmental compensation of other microtubule‐binding proteins in tau knockout mice. To circumvent these developmental compensations and assess the role of tau in the adult brain, we generated an adeno‐associated virus (AAV) expressing a doxycycline‐inducible short‐hairpin (Sh) RNA targeted to tau, herein referred to as AAV‐ShRNATau. We performed bilateral stereotaxic injections in 7‐month‐old C57Bl6/SJL wild‐type mice with either the AAV‐ShRNATau or a control AAV. We found that acute knockdown of tau in the adult hippocampus significantly impaired motor coordination and spatial memory. Blocking the expression of the AAV‐ShRNATau, thereby allowing tau levels to return to control levels, restored motor coordination and spatial memory. Mechanistically, the reduced tau levels were associated with lower BDNF levels, reduced levels of synaptic proteins associated with learning, and decreased spine density. We provide compelling evidence that tau is necessary for motor and cognitive function in the adult brain, thereby firmly supporting that tau loss‐of‐function may contribute to the clinical manifestations of many tauopathies. These findings have profound clinical implications given that anti‐tau therapies are in clinical trials for Alzheimer's disease.